Multi-Omics Analysis Reveals That SlERF.D6 Synergistically Regulates SGAs and Fruit Development - Guo, Hao; Mao, Mengdi; Deng, Yuan; Sun, Lisong; Chen, Ridong; Cao, Peng; Lai, Jun; Zhang, Yueran; Wang, Chao; Li, Chun; Li, Yiran; Bai, Qunhang; et al. (Frontiers in Plant Science, 2022)
Steroidal glycoalkaloids (SGAs) are cholesterol-derived molecules that contribute to pathogen defense in tomato but are toxic and considered to be antinutritional compounds to humans. APETALA2/ETHYLENE RESPONSIVE FACTOR (AP2/ERF) family transcription factors play an indispensable role in various biological processes, including plant growth and development, fruit ripening, biotic and abiotic stresses responses, and SGA biosynthesis. In this study, we identified 176 AP2/ERF genes that were domesticated or improved SlAP2/ERF in the tomato variome (Solanum lycopersicum) within either domestication or improvement sweeps, respectively. According to the RNA-sequencing data, 93 of the ERF genes with high transcriptional level (Transcripts Per Million, TPM > 1) belong to six clusters. Weighted gene co-expression network analysis (WGCNA) and metabolite-based genome-wide association study (mGWAS) analyses revealed that the expression level of the Solyc04g071770 (SlERF.D6) gene in cluster six gradually increased as the fruit matured. Transient transformation verified that the overexpression of SlERF.D6 significantly promoted fruit ripening and regulated the expression of multiple genes in the SGA synthesis pathway, thereby affecting the SGA content of the fruit. Virus-induced gene silencing (VIGS) showed that the silencing of SlERF.D6 delayed fruit ripening and influenced the content of SGAs. Our data provide new insights into AP2/ERF TFs in tomato, offer a candidate TF for fruit development and steroidal glycoalkaloids, and provide new resources for tomato breeding and improvement.